2018
DOI: 10.1590/1807-3107bor-2018.vol32.0112
|View full text |Cite
|
Sign up to set email alerts
|

Edema and gingival bleeding in anterior region have a negative influence on quality of life of adolescents

Abstract: The aim of the present study was to verify if clinical signs of gingivitis such as color changes, edema, and bleeding in the anterior region influence the OHRQoL of adolescents. We followed a crosssectional convenience sample of 67 adolescents aged 11 to 16 years receiving dental treatment at the Federal University of Santa Maria (UFSM), in southern Brazil. The participants were evaluated for the following clinical variables: edema, gingival color alteration, and marginal bleeding of the gingival tissues, coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…The present findings support the hypothesis that the occurrence and severity of periodontitis exert an influence on the OHRQoL of individuals with ESRD. Recent studies have reported that periodontal disease is related to OHRQoL in children (Krisdapong, Prasertsom, Rattanarangsima, & Sheiham, ; Krisdapong, Prasertsom, Rattanarangsima, Sheiham, & Tsakos, ; Tomazoni et al, ), adolescents (Lopez & Baelum, ; Maroneze, Goergen, Souza, Rocha, & Ardenghi, ) and adults (Bernabé & Marcenes, ; Brennan, Spencer, & Roberts‐Thomson, ; He, Wei, Wang, & Ji, ; Masood et al, ; Needleman, McGrath, Floyd, & Biddle, ; Tsakos et al, ). However, the association between periodontitis and OHRQoL in individuals with ESRD has not previously been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings support the hypothesis that the occurrence and severity of periodontitis exert an influence on the OHRQoL of individuals with ESRD. Recent studies have reported that periodontal disease is related to OHRQoL in children (Krisdapong, Prasertsom, Rattanarangsima, & Sheiham, ; Krisdapong, Prasertsom, Rattanarangsima, Sheiham, & Tsakos, ; Tomazoni et al, ), adolescents (Lopez & Baelum, ; Maroneze, Goergen, Souza, Rocha, & Ardenghi, ) and adults (Bernabé & Marcenes, ; Brennan, Spencer, & Roberts‐Thomson, ; He, Wei, Wang, & Ji, ; Masood et al, ; Needleman, McGrath, Floyd, & Biddle, ; Tsakos et al, ). However, the association between periodontitis and OHRQoL in individuals with ESRD has not previously been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of gingival bleeding during routine procedures, such as tooth brushing or flossing, may have influenced adolescents' perception of oral health, as gingival bleeding was self‐reported. Thus, aesthetic characteristics caused by gingival bleeding, such as edema and redness, may cause adolescent sadness and dental shame, 21,28 as well as unfavorable social responses by peers, 19,29 such as verbal bullying. This can be explained because gingival appearance is an important component of smile, being one of the fundamental physical characteristics in the development of the individual's self‐image and self‐esteem 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Dental shame was related to a higher occurrence of verbal bullying. Previous studies have shown that the presence of gingivitis, characterized by clinical signs such as enlargement and gingival bleeding, affects the overall OHRQoL and the emotional and social well‐being domains 19,21 . In this sense, individuals who are ashamed of the aesthetic appearance of the smile tend to be less confident, withdrawn and have a low self‐esteem, 32 which may be related to a higher occurrence of bullying among classmates at school, and consequently reflecting in a worse OHRQoL 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents with extremely poor backgrounds such as being from a divorced family, low family income, and low educational state of parents at baseline had higher percentage of teeth with gingival bleeding and dental caries than their counterparts 6,9 . A recent study showed that color alterations, marginal bleeding and gingival edema can be considered clinical signs of gingivitis that are associated with a worse oral health‐related quality of life (OHRQoL) in adolescents 10 . Because tooth brushing can mechanically disrupt and remove plaque, it has been emphasised as a good health behavior for prevention of caries, and brushing twice a day has become a socially accepted level; however, the evidence for frequency is unclear and conflicting 2,11 .…”
Section: Introductionmentioning
confidence: 99%